Occurrence and Distribution of Phytochemicals in the Leaves of 17 In vitro Cultured Hypericum spp. Adapted to Outdoor Conditions - Kucharíková, Andrea; Kusari, Souvik; Sezgin, Selahaddin; Spiteller, Michael; Čellárová, Eva (Frontiers in Plant Science, 2016)
A plethora of plants belonging to the genus Hypericum have been investigated so far owing to the biological efficacies of pharmacologically important secondary metabolites produced by several Hypericum species. However, there is currently a dearth of information about the localization (accumulation) of these compounds in the plants in situ. In particular, the biosynthetic and ecological consequence of acclimatization of in vitro cultured Hypericum spp. to outdoor conditions is not fully known. Herein, we report an application of matrix-assisted laser desorption/ionization high-resolution mass spectrometry (MALDI-HRMS) to reveal the distribution of major naphthodianthrones hypericin, pseudohypericin, protohypericin and their proposed precursor emodin as well as emodin anthrone, along with the phloroglucinol derivative hyperforin, the flavonoids quercetin, quercitrin, rutin and hyperoside (and/or isoquercitrin), and chlorogenic acid in Hypericum leaves. Plants encompassing seventeen Hypericum species classified into eleven sections, which were first cultured in vitro and later acclimatized to outdoor conditions, were studied. We focused both on the secretory (dark and translucent glands, other types of glands, and glandular-like structures) as well as the non-secretory leaf tissues. We comparatively analyzed and interpreted the occurrence and accumulation of our target compounds in different leaf tissues of the seventeen species to get an intra-sectional as well as inter-sectional perspective. The naphthodianthrones, along with emodin, were present in all species containing the dark glands. In selected species, hypericin and pseudohypericin accumulated not only in the dark glands, but also in translucent glands and non-secretory leaf tissues. Although hyperforin was localized mainly in translucent glands, it was present sporadically in the dark glands in selected species. The flavonoids quercetin, quercitrin and hyperoside (and/or isoquercitrin) were distributed throughout the leaves. Rutin was present only within sections Hypericum, Adenosepalum, Ascyreia and Psorophytum. Our study provides insights into the prospects and challenges of using in vitro cultured Hypericum plants, further adapted to field conditions, for commercial purposes.